The Current of Postmodern Legal Theory and its Relevance in The Development of National Law in Indonesia - Ni Nyoman Putri Purnama Santhi; Fanny Priscyllia (Westscience Press, 2026)
This article examines the current of postmodern legal theory and its relevance in the context of Indonesian law. Legal postmodernism was born as a critique of the failure of modernism projects that were considered too rigid, schematic, and ignored the complexity of social reality. Postmodern legal theory is influenced by deconstructivism, relativism, and pluralism, and is significantly influenced by the school of legal realism and Critical Legal Studies. The main characteristics of postmodern legal theory include the rejection of absolute truth, criticism of grand narratives, recognition of plurality of values, and attempts to legitimize laws that are biased in political and economic interests. In Indonesia, postmodern thought has influenced the development of law through various manifestations such as feminist legal theory and progressive law. However, the implementation of postmodern legal theory in Indonesia requires contextualization by considering the cultural values and religious norms of the Indonesian people. This study concludes that postmodern legal theory is a form of critical and dynamic theoretical reflection, which can be used to understand, study, and apply law in Indonesia, which is complex and pluralistic, noting the need for caution in deconstructing the law to remain relevant to the local context of Indonesia.